2015
DOI: 10.1038/srep16087
|View full text |Cite
|
Sign up to set email alerts
|

Metro system in Guangzhou as a hazardous reservoir of methicillin-resistant Staphylococci: findings from a point-prevalence molecular epidemiologic study

Abstract: Staphylococci are common causes of healthcare-associated and community-associated infections. However, limited data are available on the prevalence, phenotypes and molecular characteristics of Staphylococci in metro system around the world. 320 surface samples were collected from the Guangzhou metro system to isolate and characterize Staphylococci strains. Of the samples, 75.6% (242/320) were contaminated with Staphylococci. The Staphylococci isolates, especially the methicillin resistant isolates, were resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
31
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 25 publications
8
31
1
Order By: Relevance
“…According to previous study, the considerable differences in the prevalence of MRSA and S. aureus could be affected by factors such as limited sampling locations, varying sampling techniques and different regional hygiene measures (Peng et al . ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…According to previous study, the considerable differences in the prevalence of MRSA and S. aureus could be affected by factors such as limited sampling locations, varying sampling techniques and different regional hygiene measures (Peng et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…; Peng et al . ). Moreover, several studies have confirmed that environment is an important medium and vectors for dissemination of S. aureus in population (Hardy et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Clinical PCR laboratories typically have viral DNA present, enabling the development of molecular methods to detect environmental contamination. PCR was primarily developed for in vitro diagnostic use for the identification of pathogenic microorganisms . Our group uses PCR to amplify HBV DNA as an indicator of contamination under such conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This has identified global and local transmission routes and, when combined with epidemiological data, can confirm or refute putative MRSA outbreaks (Köser et al 2012;Harris et al 2013;Nubel et al 2013;Miller et al 2014;Török et al 2014;Bartels et al 2015). Similarly, while surveillance of MRSA has been carried over several years and a limited number of point prevalence studies of variable methodology have been undertaken in different settings, serial systematic prevalence studies of individual epidemic lineages are lacking (Johnson et al 2012;Afshinnekoo et al 2015;Bartels et al 2015;Peng et al 2015). WGS could potentially be used for national and local surveillance of MRSA lineages and to enhance the investigation of suspected outbreaks, but comprehensive genomic databases are required to provide the context that would allow robust epidemiological interferences.…”
mentioning
confidence: 99%